2012
DOI: 10.1017/s0950268812000544
|View full text |Cite
|
Sign up to set email alerts
|

Climate variations and salmonellosis in northwest Russia: a time-series analysis

Abstract: SUMMARYAssociations between monthly counts of all laboratory-confirmed cases of salmonellosis in Arkhangelsk, northern Russia, from 1992 to 2008 and climatic variables with lags 0–2 were studied by three different models. We observed a linear association between the number of cases of salmonellosis and mean monthly temperature with a lag of 1 month across the whole range of temperatures. An increase of 1 °C was associated with a 2·04% [95% confidence interval (CI) 0·25–3·84], 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Further to this a lag of 1 month was found in five Australian states, including SA [12]. Varying lags have been detected in other studies with temperature peaking at 1 week [20], 2 weeks [17], 1 month [11,14,15,22] and up to 2 months [13,16,18]. A lag of temperature on Salmonella spp.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Further to this a lag of 1 month was found in five Australian states, including SA [12]. Varying lags have been detected in other studies with temperature peaking at 1 week [20], 2 weeks [17], 1 month [11,14,15,22] and up to 2 months [13,16,18]. A lag of temperature on Salmonella spp.…”
Section: Discussionsupporting
confidence: 64%
“…We found an increase in daily counts of 1•3% on the overall number of salmonellosis cases per 1°C rise in maximum temperature, with greater observed increases ranging from 3•4% to 4•4% in cases depending on the serotype and phage type. Other studies examining the effect of temperature on salmonellosis found increases of 1-15% of cases per 1°C rise in temperature [11][12][13][14][15][16][17][18][19][20][21][22]. However, these estimates are based on Salmonella spp.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Study findings indicate that The positive association between temperature and salmonellosis risk in Auckland and Christchurch is consistent with previous studies from NZ 6 and elsewhere. [26][27][28] Salmonellosis tends to peak in summer and decrease in winter. 10,29 Increased temperatures could provide optimal conditions to enhance pathogen survival and multiplication and therefore increase pathogen load in food 9,10 and environmental reservoirs 30 and prolong transmission seasons.…”
Section: Discussionmentioning
confidence: 99%